(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
In Fergana region, in 1898, 11 paramedic clinics and in 1906, 16 rural district hospitals were established. The article describes the introduction of modern biomedicine to the villages of the Fergana region during the colonial period of the Russian Empire, the establishment and operation of paramedic stations and rural district hospitals.